PENGARUH KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR GEOGRAFI SISWA KELAS XI IIS SMAN 1 BANDAR SEIKIJANG KABUPATEN PELALAWAN - Medysa Gevri Rahmah; Surtani Surtani (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
The study aimed to the identify the independence of learning outcomes geography XII IIS in SMAN 1 Bandar Seikijang, 2013 curriculum based on the assement. The methodology used in thi study is the method in the form of descriptive quantitative correlational analysis. Sample obtained by using techniques proportional random sampling the proportion of as many as 60%, 56 students class XII IIS SMAN 1 Bandar Seikijang. Data collection is done by the provision of the survey. Data analysis was conducted using aid program SPSS IBM version 19.0 of analysis descriptive analysis used, that is the test of normality linearity. Based on the research reached the conclusion that is the positive and significant independence between learning and learning outcomes geography. Big the influence of independence of learning for learning outcomes geography of 88,3 % and another variable of 17%.